Current Topics in SARS-CoV-2/COVID-19 Two Years After - Rodriguez-Morales, Alfonso J. (Infectious Diseases, 2023)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has probably been the most important disease to emerge in the 21st century. This viral zoonotic disease has been a significant cause of morbidity and mortality worldwide, but with a higher impact in low- and middle-income countries of Africa, Asia, and Latin America. Up to December 4, 2022, more than 645,195,564 cases had been reported globally, with 6,640,845 deaths, and more than 13,054,668,703 doses of a vaccine had been given. Research has been of the utmost importance in the COVID-19 crisis: a great deal of knowledge was gathered between December 2019 and December 2022. Appropriate evidence-based management and the development of safe and effective vaccines have been key to controlling the virus. This book presents a selection of the last two years' learning from research and clinical practice concerning SARS-CoV-2/COVID-19.